Development of Geometry Transformation E-Module Using Contextual Teaching and Learning on Ruang GTK with GeoGebra - Aliyah Aziz; Elsa Komala; Sarah Inayah (PRISMA, 2025)
Mathematics is a basic science that is essential for mastering other sciences and continues to develop to meet the demands of the 21st century. Meaningful mathematics learning requires a contextual and technology-based approach. Kurikulum Merdeka is a government effort to address this challenge. However, obstacles remain in its implementation, such as teachers' lack of understanding of the learning modules and students' understanding of the material. Therefore, this study aims to develop a Geometry Transformation e-module using the Contextual Teaching and Learning (CTL) model in the Ruang GTK with the assistance of GeoGebra, which has been tested for its feasibility and practicality. This study uses a Research and Development (R&D) approach with the ADDIE model, through five stages: analysis, design, development, implementation, and evaluation. The research subjects consisted of three experts in material, media, language, and mathematics learning for the feasibility test and three mathematics teachers for the practicality test. The instruments used included an observation sheet, a validation sheet, and a practicality sheet. The developed e-module consists of four sub-chapters: Translation, Reflection, Rotation, and Dilation. This e-module also includes flowcharts, prerequisite materials, learning activities, teaching materials, learning media, GeoGebra, Student Worksheets (LKPD), and assessments. The study results showed that this e-module was highly feasible with a score of 85.14% and very practical with a score of 89.33%. This module is easily accessible and supports contextual and technology-based learning